METHODICAL APPROACHES IN ENGLISH TEACHING (Journal of Science-Innovative Research in Uzbekistan, 2023)
The development of a foreign language is always associated with  the selection of relevant methods. The experience of teaching English by experts of  this language is predominant. Its effective implementation and use in training  programs, including federal ones, is one of the key issues of teaching English today